2022
DOI: 10.1002/cncy.22624
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐ and intraobserver agreement in whole‐slide digital ThinPrep samples of low‐grade squamous lesions of the cervix uteri with known high‐risk HPV status: A multicentric international study

Abstract: BACKGROUND: High-risk human papilloma virus (HR HPV) testing and liquid-based cytology are used for primary cervical screening. Digital cytology, based on whole-slide scanned samples, is a promising technique for teaching and diagnostic purposes. The aim of our study was to evaluate the interobserver and intraobserver variation in low-grade squamous lesions, HR HPV status bias, and the use of whole-slide scanned digital cervical cytology slides. METHODS: Fifteen expert cytopathologists evaluated 71 digitalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…In cervical cytology, it has been demonstrated that knowledge of the high-risk HPV status may increase interobserver agreement for the ASC-US category. 19 In the case of high-risk HPV positivity, for instance, minor cellular changes can be upgraded to abnormal findings. The immunocytochemistry for p16/ ki67 might also help increase the reproducibility of interpretation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cervical cytology, it has been demonstrated that knowledge of the high-risk HPV status may increase interobserver agreement for the ASC-US category. 19 In the case of high-risk HPV positivity, for instance, minor cellular changes can be upgraded to abnormal findings. The immunocytochemistry for p16/ ki67 might also help increase the reproducibility of interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the cytopathologists interpreted anal cytology blinded to the HPV test results. In cervical cytology, it has been demonstrated that knowledge of the high‐risk HPV status may increase interobserver agreement for the ASC‐US category 19 . In the case of high‐risk HPV positivity, for instance, minor cellular changes can be upgraded to abnormal findings.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of scanned cytology slides is inferior to the microscopic picture, and the use of scanning is still mainly in teaching, quality assurance programmes, and research [4,[14][15][16][17]. Due to the characteristics of the cytopathological specimens, which contain three-dimensional groups of cells, the use of whole-slide imaging (WSI) in cytology has lagged behind that of histopathology.…”
Section: Discussionmentioning
confidence: 99%